Allelic clustering and ancestry-dependent frequencies of rs6232, rs6234, and rs6235 PCSK1 SNPs in a Northern Ontario population sample - Sirois, Francine (Springer-Verlag, 2012)
The PCSK1 (proprotein convertase subtilisin/kexin type 1) locus encodes proprotein convertase 1/3, an endoprotease that converts prohormones and proneuropeptides to their active forms. Spontaneous loss-of-function mutations in the coding sequence of its gene have been linked to obesity in humans. Minor alleles of two common non-synonymous single-nucleotide polymorphisms (SNPs), rs6232 (T > C, N221D) and rs6235 (C > G, S690T), have been associated with increased risk of obesity in European populations. In this study, we compared the frequencies of the rs6232 and rs6234 (G > C, Q665E) SNPs in Aboriginal and Caucasian populations of Northern Ontario. The two SNPs were all relatively less frequent in Aboriginals: The minor allele frequency of the rs6232 SNP was 0.01 in Aboriginals and 0.08 in Caucasians (P < 4.10(−6)); for the rs6234 SNP, it was 0.20 and 0.32, respectively (P < 0.001). Resequencing revealed that the rs6234 SNP variation was tightly linked to that of the rs6235 SNP, as previously reported. Most interestingly, all carriers of the rs6232 SNP variation also carried the rs6234/rs6235 SNP clustered variations, but not the reverse, suggesting the former occurred later on an allele already carrying the latter. These data indicate that, in Northern Ontario Aboriginals, the triple-variant PCSK1 allele is relatively rare and might be of lesser significance for obesity risk in this population. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12687-012-0081-5) contains supplementary material, which is available to authorized users.